PENERAPAN BISNIS PLAN PADA USAHA MIE GACOAN - Rini Wijayaningsih; Ananda Ummu Thoyibah; Dika Febriansyah; Marcellita Capritalim; Rani Anggitasari; Saibatul Aslamiyah; Muhammad Wallid Alba; Yefta Berliana; Tegar Bima Rohaedi (Cahaya Ilmu Bangsa, 2024)
nama